ANALISIS LOYALITAS KONSUMEN PERBANKAN SYARIAH DI SUMATERA BARAT - Roni Andespa; Rangga Wisanggara; Faznil Husna S. Rasyad (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
This study aims to analyze the loyalty of Islamic bank customers in West Sumatra. The object of research is all Islamic banks operating in West Sumatra. The population of this study is all Islamic banking customers in the province of West Sumatra. The research sample is 200 Islamic bank customers. The technique used in sampling is a non probability sampling method using Convenience sampling. The level of customer loyalty can be seen from the level of brand loyalty. In general, customer loyalty to Islamic banks in West Sumatra is very good or loyal. This can be seen from the value of the possibility of brand transfer (ProT) of Islamic banks in West Sumatra is (25.5%) and the Atrition Rate is (3%), these results indicate the percentage of a customer moving to another company, which is obtained from the reduction in the value of ProT with a percentage of non-loyal values.